Sensores eletroquímicos para o fármaco cisplatina como ferramenta biotecnológica no monitoramento clínico, metabólico e ambiental - Materón Vásquez, Elsa María [UNESP] (2015)
This thesis presents the development of two electrochemical sensors for the sensitive and selective detection of cisplatin, one of the drugs most frequently used in the oncologic treatment of several cancer tumor pathologies. The first was a biosensor based on carbon paste modified with the enzyme glutathione-s-transferase (GST). The biosensing was based on the inhibitory response of the enzymatic activity of GST due to the addition of the drug cisplatin. Reduced glutathione (GSH) and 1-chloro-2,4-dinitrobenzene were used as substrates for the GST enzyme, and were added at the concentration of 1.0 x 10-3 mol L-1 in the measuring cell. The techniques used for the characterization of the system were infrared spectroscopy, cyclic voltammetry and electrochemical impedance. The quantitative results of those interactions, obtained by square wave voltammetry (SWV) and differential pulse with adsorptive stripping voltammetry were very similar, and very promising for the analysis of cisplatin. The biosensor showed, using SWV, a linear response between 50 and 140 μmol L-1 of cisplatin. The detection limit was 8.8 μmol L-1 of cisplatin. In the intra-day repeatability studies, the relative standard deviation was 4.2%, from the analysis of four analytical curves, showing the repetitiveness of the electrochemical response of the proposed sensor. The use of the carbon paste offered the possibility of the simple, quick and efficient renewal of the surface layer of the electrode, which allowed the use of the same paste for several measurements during a long period of time. Additionally, a non-enzymatic sensor was developed for the monitoring of cisplatin using screen-printed carbon electrodes (SPCE, screen-printed carbon electrodes), functionalized with multi-walled carbon nanotubes and factory modified with carboxyl groups (MWCNT-COOH) acquired from DROPSENS® (SDS 110CNT). The electrochemical characterization...